KEMAMPUAN PEMBUKTIAN MATEMATIS MAHASISWA MATEMATIKA PADA MATA KULIAH TEORI BILANGAN - Cut Multahadah (JURNAL GAMMA-PI, 2022)
Number Theory is one of the courses in the Mathematics Study Program. The learning achievement in this course is being able to prove the theorem contained in a set of integers. To prove the theorem requires mathematical proof ability. The ability to prove mathematically requires students to be able to analyze, sort and relate the facts given in the form of premises and conclusions. One of the strategies in mathematical proof is direct proof. This study focuses on the description of the mathematical proof ability of students of the mathematics study program for the academic year 2022/2023, totaling 26 people in the Number Theory course on the topic of division related to direct proof strategies. This research is a qualitative and quantitative research with technical data analysis using the Miles and Huberman Model and Tests. The results showed that from 26 students 42.308% percent answered perfectly, 15.384% students answered imperfectly and 42.308% percent of students answered incorrectly. So it can be concluded that the students' mathematical proof ability, especially the problem of direct proof in the Mathematics study program, Faculty of Science and Technology, Jambi University, in the Number Theory course is 57.692% in the good category and 42.308% in the bad category.